Teaching English Through Literature and Connecting with Language Teaching - Amanova Nodirabegim Furkatovna (Euro Asian Journal Publishing, 2024)
Writing plays an imperative part in educating four essential dialect aptitudes such as perusing , composing , tuning in , and talking . In any case , when utilizing dialect classroom writing , aptitudes ought to never be instructed in confinement but in an coordinates way. Instructors ought to endeavor to instruct essential dialect aptitudes as an fundamentally portion of verbal and composed dialect utilize , as portion of instruments to form both reference and intuitively meaning, not fair word As an angle of mental and composed generation , expressions and idioms
Keywords: imaginative literature; foreign language; integrated language